Synthesis and Characterization of Some Transition Metal Chelates of 2,2’-Dithiobenzoic Acid - G. Bhowon, Minu; Jhaumeer-Laulloo, Sabina; Rungasami, Preeti (Asian Journal of Chemistry, 2010)
2,2'-Dithiobenzoic acid (1) metal complexes (1a-4a, 1b-4b, 1c- 4c) were synthesized using 1 and metal salts such as copper(Il), cobalt(II), manganese(Il), nickel(Il), zinc(II) acetates and ruthenium (III) chlorides in the absence or in the presence of diamines. The analytical and spectroscopic data of all complexes confirmed an octahedral geometry around the central metal ion with water molecules occupying the coordination sphere. Some of the metal complexes display antibacterial activity.